Penerapan Metode Economic Order Quantity (EOQ) Terhadap Pengendalian Persediaan Bahan Baku Pada Percetakan MD Drafika - Maulana, Anwar; Herdian, Faldy (Lembaga Pengembangan Kinerja Dosen, 2025)
Currently, MD Drafika faces challenges due to a lack of proper inventory management, such as safety stock regulations and reorder schedules. This has led to inventory levels that often fail to meet customer demand. The objective of this research is to optimize inventory costs at MD Drafika to enhance cost efficiency. This study employs a descriptive quantitative method, utilizing data collected through observation and interviews to explain the relevant aspects of the research object. The results of the research reveal an optimal order quantity and a reduction in inventory costs. Inventory optimization was achieved by adjusting safety stock levels and reorder points. The calculations for 2023 showed an optimal order quantity of 3,349 pieces, with four purchasing cycles within the period. The safety stock was determined to be 945 pieces, and the reorder point was 992 pieces. The cost difference between the EOQ method and the company’s current approach amounted to IDR 1,179,928.